Time to care—Care for time—How spending more time for care than consumption helps to mitigate climate change - Smetschka, Barbara; Gaube, Veronika; Mader, Katharina (Frontiers in Sustainability, 2023)
Mitigating climate change requires urgent reductions of emissions. Demand-side measures focus on footprints (direct and indirect emissions) of consumption. Analyzing time use brings a novel perspective to discuss the carbon implications of everyday life and the potentials and limitations for decarbonizing consumption. In this paper we show how time-use studies can serve as a bridging concept between sustainability studies and the analysis of human well-being for all. We introduce a functional time-use perspective differentiating personal, committed, contracted and free time. We calculate average carbon intensity of everyday activities in Austria 2010 combining Austrian Time-use Survey and Austrian Household Budget Survey with Eora-MRIO. We find that these activities differ widely in carbon intensity. Personal time is relatively low-carbon intense, while free time activities show large variation in terms of CO2e footprint/hour. The traditional gendered division of labor shapes the time-use patterns of women and men, with implications for their carbon footprints. Reassessing and sharing unpaid reproductive caring activities is the basis for solving some urgent ecological and social problems. The way household members use their time, the resource demand of households and infrastructure and services provided by communities entail each other. Time use, time prosperity and especially time scarcity determine our quality of life. Caring activities as “time to care” play a crucial role for pathways towards socio-ecological transformation and gender equality. Further research in the field of time, care and gender studies could be based on this framework and add new perspectives on research on sustainable development.